Síntese e estudo da estabilidade conformacional de S-nitrosotiós derivados de AINEs (anti-inflamatórios não esteróidais) - Reginato, Marcelo Mota [UNIFESP] (2014)
We synthesized and carried out a conformational study of the S-nitrosothiols 2-methyl-2-(nitrososulfanyl) propyl-phenylacetate-para-substituted 9R1, derivative of propanoic 2-(4-isobutylphenyl) acid (Ibuprofen) 9R2 and 2-methyl-2-(nitrososulfanyl) propyl 2-(4-isobutylphenyl) propanoate (Naproxen) 9R3 (S-Nitrosothiols 9R1, 9R2, and 9R3): Two synthetic routes have been proposed for the synthesis of S-Nitrosothiols 9R1, 9R2, and 9R3. In Route A we used brominated intermediates and dicyclohexylcarbodiimide (DCC) as coupling reagent for esterification. In Route B the esterification with an acyl chloride is the last step in the synthetic route. Both routes resulted in good yields of the final product (~ 50%), although only Route B led to the formation of the compounds of interest. S-Nitrosothiols 9R1, 9R2, and 9R3, together with their brominated intermediates were submitted to infrared spectroscopic analysis in solvents of low dielectric constant (CCl4, CH3Cl and CH3CN). For brominated intermediates we observed the presence of two bands in the carbonyl stretch region of the group indicating the existence of two conformations. S-Nitrosothiols 9R1, 9R2, and 9R3 showed only one band in the same region in most cases. We carried out the conformational search for the compounds under study and stable conformations geometries were theoretically optimized, B3LYP DFT / G 6311 + (2df, 2p). Results obtained in the infrared analysis were confronted with the theoretical data showing good agreement with experimental results in CCl4 for isolated molecules. Calculations made using the solvent effect by the method PCM do not indicate agreement with experimental data. The lowest energy conformations of S-Nitrosothiols 9R1, 9R2, and 9R3 and brominated intermediates are mainly stabilized by intra-molecular hydrogen bonds that promote greater stability of conformers. The geometrical analysis of the R-SNO group shows that these compounds are more stable in the trans conformation. Calculations of orbital interactions for the brominated intermediates using the method of Natural Bond Orbital (NBO) showed no electronic interactions capable of stabilizing their conformations. The NBO based calculations for the S-Nitrosothiols 9R1, 9R2, and 9R3 show that their conformers are stabilized by the following interactions: n_(O(OR)) 〖→ σ〗_(C-C(CO))^*, n_(O(OR))→σ_((CO))^*, n_(O(CO))→σ_((CO))^*, n_(O(CO))→〖 π〗_(C14-O15)^*, n_S→π_((NO))^*, e n_(O(NO))→σ_((S-N))^*. NBO results showed that the hyper-conjugative interaction n_(O(NO))→σ_((S-N))^* is very effective, weakening the σ bond resulting in increasing length of the S-N bond in R-SNO. The strong delocalization n_S→π_((NO))^*induces partial π character to the S-N bond. The weak link σ S-N indicates a strong delocalization of the electron pair of O(NO) due to interaction n_(O(NO))→σ_((S-N))^* . This interaction is responsible for the elongation of the S-N bond which increases the ability of the compound in releasing nitric oxide. The molecular mechanism of esterification using DCC was investigated by using electronic structure calculations on DFT-B3LYP / 6 311 + G (2df, 2p) level. We described two pathways for the esterification reaction: (i) concerted model (one step leads to the formation of products) and (ii) non-coordinated model (two steps followed by a [1-3] proton migration leads to the formation of products). Results were discussed in terms of energy, electronic parameters and calculated geometries of reactants under study (carboxylic acid, alcohol and DCC) and the reaction product (ester). The activation energy for the concerted model was lower (G‡ 27.8 kcal.mol-1) than for the non-coordinated model (G‡ 48.9 kcal.mol-1). This step was considered as a determinant of the reaction.